2014
DOI: 10.2971/jeos.2014.14054
|View full text |Cite
|
Sign up to set email alerts
|

Low-cost resonant cavity Raman gas probe for multi-gas detection

Abstract: Raman based gas sensing can be attractive in several industrial applications, due to its multi-gas sensing capabilities and its ability to detect O 2 and N 2 . In this article, we have built a Raman gas probe, based on low-cost components, which has shown an estimated detection limit of 0.5 % for 30 second measurements of N 2 and O 2 . While this detection limit is higher than that of commercially available equipment, our estimated component cost is approximately one tenth of the price of commercially availabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 27 publications
(28 reference statements)
0
10
0
Order By: Relevance
“…Such feedback loops may either adjust the optical frequency of the laser to match the cavity frequency, or adjust the cavity length via a piezoelectric actuator. A number of different techniques have been used for locking the cavity into a resonance state [30,[56][57][58].…”
Section: Mode Lockingmentioning
confidence: 99%
See 2 more Smart Citations
“…Such feedback loops may either adjust the optical frequency of the laser to match the cavity frequency, or adjust the cavity length via a piezoelectric actuator. A number of different techniques have been used for locking the cavity into a resonance state [30,[56][57][58].…”
Section: Mode Lockingmentioning
confidence: 99%
“…However, a number of different approaches have been proposed to enhance the signal such as confining light in a fiber (Fiber Enhanced Raman Spectroscopy (FERS)) or amplifying the signal by using a resonant mirrored cavity. Cavity Enhanced Raman Spectroscopy (CERS) uses the ability of mirrored cavities to enhance the input power, by tuning the cavity to particular modes of the input laser wavelength [29,30]. The approach takes advantage of the availability of affordable mirrors with high reflectivity surfaces, controllable mirror support bases, and inexpensive detection capabilities using low cost detectors or arrays.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Raman gas analysis, because of low intensity of informative signals caused by small scattering cross-sections and low density of molecules in the gas phase, is less developed. However, interest in this direction of research has recently increased [3][4][5][6] due to the active development of hollow-core fibers, [7][8][9][10][11][12] appearance of high-power small-sized lasers and high-sensitive multichannel photodetectors. 13,14 In addition, it should be noted that nowadays first commercial Raman gas analyzers 15 start to appear, and despite the fact that their sensitivity is relatively low (0.01%) so far, there is a great potential for the development of this direction.…”
Section: Introductionmentioning
confidence: 99%
“…11 With the active development of surface-enhanced Raman scattering (SERS) and the appearance of hollow-core fibers, high-power small-sized lasers, and high-sensitivity multichannel photodetectors, more gas-sensing studies have emerged. [14][15][16][17] In 2014, Hanf et al reported a fiber-enhanced Raman spectroscopy system for multigas analysis. 18 In 2015, Deng et al proposed a headspace thin-film microextraction technique that was coupled with SERS to detect sulfur dioxide in wine.…”
Section: Introductionmentioning
confidence: 99%